Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am currently in the middle of the following problem.

Reparametrize the curve $\vec{\gamma } :\Bbb{R} \to \Bbb{R}^{2}$ defined by $\vec{\gamma}(t)=(t^{3}+1,t^{2}-1)$ with respect to arc length measured from $(1,-1)$ in the direction of increasing $t$.

By reparametrizing the curve, does this mean I should write the equation in cartesian form? If so, I carry on as follows.

$x=t^{3}+1$ and $y=t^{2}-1$

Solving for $t$




Letting $y=f(x)$, the arclength can be found using the formula

$$s=\int_{a}^{b}\sqrt{1+[f'(x)]^{2}}\cdot dx$$

Finding the derivative yields




Putting this into the arclength formula, and using the proper limits of integration (found by using $t=1,-1$ with $x=t^{3}+1$) yields

$$s=\int_{0}^{2}\sqrt{1+\frac{4}{9(x-1)^{2/3}}}\cdot dx$$

I am now unable to continue with the integration as it has me stumped. I cannot factor anything etc. Is there some general way to approach problems of this kind?

share|cite|improve this question

As given curve is not regular when $t=0$ and your curve parameter runs from $-1$ to $1$, Hence Below is arc lengh parameter of the curve from $0$ to $1$. And same will work for $0$ to $-1$.

What is arc length formula, when curve is given parametric form as in your case $$\gamma (t)= (t^3+1, t^2-1)$$

Arc length formula is $$s(t)= \int_{1}^t\|\gamma'(t)\|dt$$

That is we have $$s(t)=\int_{1}^t\|(3t^2, 2t)\|dt$$
$$s(t)=\int_{1}^t t\sqrt{9t^2+4} dt$$ $$s(t)= \left[\frac{(4+9t^2)^\frac{3}{2}}{27}\right]_{1}^t$$ $$s(t)= \frac{(4+9t^2)^\frac{3}{2}-13^\frac{3}{2}}{27}$$

which gives $$t(s)= \left(\frac{(27s+13^\frac{3}{2})^\frac{2}{3}-4}{9}\right)^\frac{1}{2}$$

Putting the value of $t$ in $\gamma(t)$, you will have $\tilde{\gamma}(s)=\gamma(t(s))$ arc length parameterization..

share|cite|improve this answer

Reparametrizing the curve in terms of arc length from a base point means rewriting the equation of the curve so that it tells you what point is at distance $s$ from the base point for any given $s$.

It’s easier to find the arc length parametrization directly. Let $s(u)$ be the length of the arc from $t=0$ (since that’s the value of $t$ that yields the point $\langle 1,-1\rangle$) to $t=u$; then

$$\begin{align*}s(u)&=\int_0^u\sqrt{\left(\frac{dx}{dt}\right)^2+\left(\frac{dy}{dt}\right)^2}dt\\ &=\int_0^u\sqrt{(3t^2)^2+(2t)^2}dt\\ &=\int_0^u\sqrt{t^2(9t^2+4)}dt\\ &=\int_0^ut\sqrt{9t^2+4}dt\\ &=\frac1{27}\left[(9t^2+4)^{3/2}\right]_0^u\\ &=\frac1{27}\left((9u^2+4)^{3/2}-8\right)\;. \end{align*}$$

Replace $u$ by $t$: the length of the arc from $\langle x(0),y(0)\rangle$ to $\langle x(t),y(t)\rangle$ is $$s(t)=\frac1{27}\left((9t^2+4)^{3/2}-8\right)\;,$$ so $$t(s)=\left(\frac19(27s+8)^{2/3}-4\right)^{1/2}\;.$$

This gives you the value of $t$ that specifies the point on the curve that is $s$ units from the initial point $\langle 1,-1\rangle$; to finish the job, you just need to express $x$ and $y$ as functions of $s$, which is a straightforward substitution into the $x(t)$ and $y(t)$ formulas.

share|cite|improve this answer


Substitute $(x-1)^{1/3}=t$. Your integral will boil down to $$\int_{-1}^1t\sqrt{4+9t^2}\rm dt$$

Now set $4+9t^2=u$ and note that $\rm du=18t~~\rm dt$ which will complete the computation. (Note that you need to change the limits of integration while integrationg over $u$.)

A Longer way:

Now integrate by parts with $u=t$ and $\rm d v=\sqrt{4+9t^2}\rm dt$ and to get $v$, you'd like to keep $t=\dfrac{2\tan \theta}{3}$

share|cite|improve this answer
you can substitute $4+9t^2= x$ and then proceed.. – zapkm Mar 1 '12 at 3:54
@PradipMishra Thank You. I don't know why I could not think of this! Thank you for the pointer! – user21436 Mar 1 '12 at 4:13

Your integration could be done. However, there is a much easier way. Calculate the arc-length using the parametric version of the curve.

We have $x=u^3+1$ and $y=u^2-1$. (I changed the names of the parameters because I want to reserve $t$ for the parameter of the endpoint.) Then $\frac{dx}{du}=3u^2$ and $\frac{dy}{du}=2u$. Thus the arclength from $u=0$ to $u=t$ is given by $$\int_0^t \sqrt{\left(\frac{dx}{du}\right)^2 +\left(\frac{dy}{du}\right)^2}\,du.$$ We have used the parametric arclength formula, much easier! The integration starts at $u=0$, since that is the value of the parameter that gives us the point $(1,-1)$.

We end up integrating $\sqrt{9u^4+4u^2}$. Since $u\ge 0$, we can replace this by $u\sqrt{9u^2+4}$. Integrate, making the substitution $w=9u^2+4$. We arrive at $$\frac{1}{27}\left((9t^2+4)^{3/2}-8\right).\qquad (\ast)$$ This is the arclength $s$, expressed as a function of $t$.

We want to parametrize in terms of $s$. So solve for $t$ in terms of $s$, using $(\ast)$. When you solve, there will be two candidate values of $t$. Take the non-negative one, since we started at $t=0$ and were told that t$ is increasing.

Finally, in the original parametrization, replace $t$ by its value in terms of $s$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.